Immune-Mediated Neutropenia and Thrombocytopenia in a Patient with Ulcerative Colitis: An Unusual Hematological Association with IBD - Young-In Kim; Aaron Brzezinski; Joseph Brandwein; Jeffrey P Baker (Canadian Journal of Gastroenterology)
Hematological manifestations of inflammatory bowel disease (IBD) are well described in the literature. However, the combination of immune-mediated neutropenia and thrombocytopenia has only been reported once in association with IBD. A case is reported of immune-mediated neutropenia and thrombocytopenia in a patient with ulcerative colitis during a relapse. No obvious causes of these hematological abnormalities were found in the patient despite an exhaustive search. An immune-mediated process was confirmed by positive antineutrophil antibody and platelet-associated antibody in the patient’s serum, and the demonstration of binding of the patient’s immunoglobulin G to autologous neutrophils. The patient was treated with high-dose steroid, intravenous gamma-globulin and eventually splenectomy. The platelet count subsequently normalized; although the severe neutropenia recurred, it has subsequently improved without further treatment. Although a definitive cause-effect relationship cannot be established, the immune-mediated neutropenia and thrombocytopenia may be an unusual hematological manifestation associated with ulcerative colitis.